2013
DOI: 10.1002/oby.20383
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obese adult humans have a defective cellular immune response to pandemic H1N1 Influenza a virus

Abstract: Objective Obese adults have a greater risk of morbidity and mortality from infection with pandemic H1N1 influenza A virus (pH1N1). The objective of the present study was to elucidate the specific mechanisms by which obesity and overweight impact the cellular immune response to pH1N1. Design and Methods We stimulated peripheral blood mononuclear cells from healthy weight, overweight, and obese individuals ex vivo with live pH1N1 and then measured markers of activation and function using flow cytometry and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
138
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 24 publications
5
138
0
3
Order By: Relevance
“…Recently, two human studies have supported this hypothesis and observed inhibited T cell activation and expression in IAV-vaccinated obese individuals [69, 74]. In one study [69], peripheral blood mononuclear cells (PBMCs) were obtained from obese subjects 12 months after immunization with the 2010–2011 seasonal IAV vaccine.…”
Section: Influenza a Virus (Iav)mentioning
confidence: 99%
“…Recently, two human studies have supported this hypothesis and observed inhibited T cell activation and expression in IAV-vaccinated obese individuals [69, 74]. In one study [69], peripheral blood mononuclear cells (PBMCs) were obtained from obese subjects 12 months after immunization with the 2010–2011 seasonal IAV vaccine.…”
Section: Influenza a Virus (Iav)mentioning
confidence: 99%
“…Furthermore, the evidence that macrophage phagocytic activity was impaired in obese mouse models indicated that innate immunity is defective in obesity (56,57). T cells (86). Thus, defects of CD4+ T cells impact on antibody production by B cells.…”
Section: Characterizations Of Related Immune Cells In Obesity Macrophagementioning
confidence: 99%
“…Obesity: Obesity has commonly been reported in ICU submissions and patients dying from pdm(H1N1)09 [6,11,12,[15][16][17][18] and has been identified as a predictor of outcome in acute respiratory infection [19], possibly as a consequence of a defective cellular immune response to infection [20]. Of those admitted to an ICU in Australia and New Zealand in 2009, 28.6% (of which data was available) had a BMI of 35 kg/m 2 or greater [12].…”
Section: Factors Associated With Death or Hospitalisationmentioning
confidence: 99%